Implementação do cálculo do Fator de Cholesky diretamente a partir da matriz de rigidez do elemento estrutural - Prates, Carlos Leopoldo Martins (1979)
In a static analysis the unknowns may be found by rneans of obtaining a factor of the stiffness matrix of the structure. The most popular solution method involves the transformation of this matrix into an upper triangular matrix, the Cholesky factor. Here, it is shown how this factor may be obtained directly from the factor of the elemental stiffness matrix and a representative factor of the structural matrix. The results from the computers program which was developed for the new method have garanteed its precision and the advantage of employing it to solve ill-conditioned problems. The basic ideas of this formulation were developed in Germany by other authors for the ASKA system. These ideas have been worked up here, an automatic program has been obtained for bearn and triangular finite elements and some suggestions are given for the further development of the new method.